An evaluation model of islamic learning education program in madrasah aliyah - Anidi Anidi (Graduate School, Universitas Negeri Yogyakarta, 2017)
The purpose of this study is: (1) to create the products as the evaluation model learning programs of Islamic education in madrasah aliyah, suitable, precise, and accurate, (2) to know how to test the suitability of the model to obtain the evaluation model of Islamic Education learning programs in madrasah aliyah which is valid, and reliable, and (3) determine the effectiveness of the application of evaluation model of Islamic learning programs that was developed. This was a research and development method study (R D), referring to the model of Borg Gall, the development process was simplified into three steps, namely: (1) the stage predevelopment of models, (2) the stage of development of the model, and (3) the operational phase of the field (test model). The data were collected using questionnaires, interview, observation, documentation, and test. Data were analyzed using quantitative and qualitative. The conclusion of this research and development is: (1) evaluation model of Islamic Religious Education Learning program developed comprising: (a) the evaluation procedures, (b) the evaluation instrument, and (c) the evaluation guide. (2) according to the experts, PAI teachers, and principals, procedures, instruments, and evaluation guidelines developed are already good, and can be used, d) the instrument developed is entirely valid (load factor 0.3), reliable (CR 0.7), and qualified as a fit model (RMSEA ≤ 0.08 and NFI, CFI and GFI .90). second, the expert's opinion, PAI teachers and principals, the developed evaluation model (EPH model) is declared effective, practical, and easy to use, and supported by a valid and reliable instrument.